The Emergence and Maintenance of a Deviant Sub-Culture: The Case of Hunting/Poaching Sub-Culture - Brymer, Richard A. (Anthropologica, 2022)
Few accounts of deviant sub-culture properly examine their historical context and relationship to the dominant culture. This paper attempts to achieve both goals. It is an account of the social organization and practice of members of the hunting/poaching sub-culture in North America. An historical ethnographic description of poachers includes a description of the sub-culture and the strategies adopted by members both to deal with the increasing technological sophistication of regulators and to achieve social control within their own small-scale group.